Association of the belief in conspiracy narratives with vaccination status and recommendation behaviours of German physicians - Taubert, Frederike; Schmid, Philipp; Holford, Dawn; Verger, Pierre; Fasce, Angelo; Karlsson, Linda C.; Soveri, Anna; Lewandowsky, Stephan; Betsch, Cornelia (Elsevier BV, 2025)
Vaccine hesitancy has been identified as one of the top ten threats to global health by the World Health Organization (WHO). The belief in conspiracy narratives is repeatedly discussed as a major driver of vaccine hesitancy among the general population. However, there is a lack of research investigating the role of the belief in conspiracy narratives in vaccination decisions and recommendation behaviours of physicians. This is particularly relevant as physicians are one of the major and trusted sources of information for patients' vaccination decisions. This study therefore investigated the association between believing in COVID-19-related conspiracy narratives and physicians' own COVID-19 vaccination status and their recommendation behavior for COVID-19 and other vaccines (e.g., HPV or flu). In a cross-sectional survey among German physicians (N = 602, April 2022) two conspiracy narratives were assessed, stating that the coronavirus is a hoax or that it is human-made. Additional control variables included trust in health institutions, the rejection of complementary and alternative medicine (CAM), the 5C psychological antecedents of vaccination (confidence, complacency, constraints, calculation, and collective responsibility) and demographic variables. Hierarchical regressions indicated that greater belief in the conspiracy narrative claiming that the coronavirus is a hoax was associated with lower COVID-19 vaccination uptake and fewer COVID-19 vaccination recommendations among physicians. The results for recommendation behavior remain robust even when controlling for other variables. Contrary to our assumption, believing that the coronavirus is human-made was not related to vaccination status nor vaccine recommendation behavior. In conclusion, believing in conspiracy narratives that question the existence and thus also the danger of the virus is an important independent predictor of vaccine hesitancy among physicians that should be addressed in future public health interventions.